2011
DOI: 10.3892/ol.2011.341
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic discrimination of sessile serrated adenomas from other serrated lesions

Abstract: Abstract. Sessile serrated adenoma (SSA) is a proposed precursor of colorectal carcinogenesis. This study aimed to analyze the potential of endoscopy to discriminate SSA from other serrated lesions, specifically traditional serrated adenoma (TSA) and hyperplastic polyp (HP). Of 145 serrated lesions, 111 sessile serrated lesions including 32 TSAs, 25 SSAs and 54 HPs were analyzed for size, color, location and morphologic features using conventional endoscopy and magnifying chromoendoscopy. SSA was preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…SSAs, which are typically larger than HPs and located in the proximal colon, are flat or non-polypoid in morphology [62], often with the appearance of redundant or thickened mucosa altering the contour of a fold, or appearing to be draped over a fold (Fig. 3) [63, 64]. A distinctive feature of SSAs is the mucus cap, comprising a layer of mucus adherent to the surface of the lesion, giving the lesion a yellow or rust-colored appearance in contrast to the surrounding mucosa [65].…”
Section: Colonoscopic Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…SSAs, which are typically larger than HPs and located in the proximal colon, are flat or non-polypoid in morphology [62], often with the appearance of redundant or thickened mucosa altering the contour of a fold, or appearing to be draped over a fold (Fig. 3) [63, 64]. A distinctive feature of SSAs is the mucus cap, comprising a layer of mucus adherent to the surface of the lesion, giving the lesion a yellow or rust-colored appearance in contrast to the surrounding mucosa [65].…”
Section: Colonoscopic Detectionmentioning
confidence: 99%
“…These characteristics were confirmed in a recent prospective study of 158 SSAs in which dominant features included a mucus cap, a rim of bubbles or debris, alteration of the contour of a fold, and loss of the normal mucosal vascular pattern (Table 3). TSA are typically located distally, are more bulky, and tend to be pedunculated or sessile [64].
Fig.
…”
Section: Colonoscopic Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of improvements in endoscopic imaging, details of the colorectal mucosa surface can be observed with colonoscopies. However, several studies 11 12 have reported a low diagnostic accuracy of any of the novel endoscopic imaging techniques for differentiating SSAs from HPs. However, Kimura et al 13 have proposed a type II open-shape pit pattern (Type II-O) which was specific to SSA/Ps.…”
Section: Introductionmentioning
confidence: 99%